(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Community Extension Programs is an activity where an individual can experience a different way of learning. It doesn’t teach what is written in the book but how to apply it in the outside world. Moreover, the meaning of Community Extension Programs varies to every person. It somehow kind and caring to others or to help out those who are less fortunate. The study aimed to determine the extent of implementation of the Extension Services of Abra State Institute of Sciences and Technology. Specifically, it sought to answer the following questions: how effective are the strategies in the implementation of the Extension Programs of ASIST? What is the extent of implementation of the Extension Programs of ASIST? Is there a significant relationship between the effectiveness of strategies and the extent of implementation of the Extension Programs of ASIST? What are the challenges in the implementation of the Extension Programs of ASIST Findings of the study revealed that; Training services has the highest mean value of 4.49 described as Very Much Implemented. Information and Communication services has the highest mean value of 3.98 described as Much Implemented. There is a significant relationship between the effectiveness of strategies and the extent of implementation of extension services of Abra State Institute of Sciences and Technology. Financial challenges has the highest mean value of 3.75 described as Moderately serious. Most of the program implementers perceived the level of effectiveness of strategies in training services. Most of the program implementers perceived the extent of implementation in Information and communication services. The null hypothesis is rejected since there is a significant relationship between the effectiveness of strategies and the extent of implementation of extension services among the program implementers of Abra State Institute of Sciences and Technology. Program implementers perceived that most of the enumerated financial challenges were moderately serious to affect their extension programs. The Extension Department should come up with sustainability plan in order to uplift other services. The Extension Department should strengthen more other programs and look into the increase of frequency of the Radyo Kabinulig in order that the programs to be aired will be province wide. Program implementers should look for more linkages from the different agencies and organizations such as local, national and international arena. From the shortcomings of the implementers as being analyzed from the study, it is hoped that these should not be taken negatively, but rather should serve as a basis for reliable assessment and evaluation for the improvement of the implementation process.